Descriptive cohort study of Ligation of femoral artery in infected femoral pseudoanurysm in injectable drug abuser - Chapagain, Dinesh; Shrestha, Kiran Prasad; Magar, Deepak Thapa; Shrestha, Kumar Bahadur (Nepal Mediciti Medical Journal, 2020)
Background: Infected femoral pseudoanurysm with impending rupture presents most of the time in the late stage in drug abuser with features of sepsis. These cases are managed immediately by exploration with ligation of femoral artery when bypass is not feasible in emergency.Methods: This is the retrospective descriptive study of 11 years of bir hospital. Datas were collected from the record and subsequent out patient department visits of the cases having femoral infected pseudoanurysm with impending rupture with sepsis of injectable drug abuser. The data collected were patients profile, type of procedure like ligation of femoral artery, bypass like reverse long saphenous graft and synthetic dacron or ptfe graft and complications were also recorded with subsequent. The type of procedure were compared with amputation as final end point. Datas were analysed by SPSS softwear.Results: We recorded the datas of 45 patients with almost all were male with very few female having mean age of 27.91 years. Twenty two patients had seropositive status and 13 patients had negative. Thirty five patients had ligation of femoral artery,7 patients had interposition synthetic bypass graft and 3 patients had reversed long saphenous vein graft. Nine patients had undergone revision after graft failure as ligation. No complication in 20 cases .Nine cases had rethrombosis with infection, 7 had minor complication and 1 had severe claudication.Conclusions: In emergency setting, simple ligation of the femoral artery can be both life and limb saving procedure in difficult situation like infection and sepsis.